Cytotoxic Effects of Arsenite in Combination With Gamabufotalin Against Human Glioblastoma Cell Lines - Yuan, Bo; Xu, Kang; Shimada, Ryota; Li, JingZhe; Hayashi, Hideki; Okazaki, Mari; Takagi, Norio (Frontiers in Oncology, 2021)
Glioblastoma is a fatal primary malignant brain tumor, and the 5-year survival rate of treated glioblastoma patients still remains < 5%. Considering the sustained development of metastasis, tumor recurrence and drug resistance, there is an urgent need for the novel therapeutic approaches to combat glioblastoma. Trivalent arsenic derivative (arsenite, AsIII) with remarkable clinical efficacy in leukemia has been shown to exert cytocidal effect against glioblastoma cells. Gamabufotalin, an active bufadienolide compound, also shows selective cytocidal effect against glioblastoma cells, and has been suggested to serve as a promising adjuvant therapeutic agent to potentiate therapeutic effect of conventional anticancer drugs. In order to gain novel insight into therapeutic approaches against glioblastoma, the cytotoxicity of AsIII and gamabufotalin was explored in the human glioblastoma cell lines U-87 and U-251. In comparison with U-251 cells, U-87 cells were highly susceptible to the two drugs, alone or in combination. More importantly, clinically achieved concentrations of AsIII combined with gamabufotalin exhibited synergistic cytotoxicity against U-87 cells, whereas showed much less cytotoxicity to human normal peripheral blood mononuclear cells. G2/M cell cycle arrest was induced by each single drug, and further augmented by their combination in U-87 cells. Downregulation of the expression levels of cdc25C, Cyclin B1, cdc2 and survivin was observed in U-87 cells treated with the combined regimen and occurred in parallel with G2/M arrest. Concomitantly, lactate dehydrogenase leakage was also observed. Intriguingly, SB203580, a specific inhibitor of p38 MAPK, intensified the cytotoxicity of the combined regimen in U-87 cells, whereas wortmannin, a potent autophagy inhibitor, significantly rescued the cells. Collectively, G2/M arrest, necrosis and autophagy appeared to cooperatively contribute to the synergistic cytotoxicity of AsIII and gamabufotalin. Given that p38 MAPK serves an essential role in promoting glioblastoma cell survival, developing a possible strategy composed of AsIII, gamabufotalin and a p38 MAPK inhibitor may provide novel insight into approaches designed to combat glioblastoma.